Cambridge international AS & A level Mathematics : Probability & Statistics 1 coursebook - Chalmers, Dean; Gilbey, Julian (New York : Cambridge, 2018)
This coursebook is meticulously designed to support students in mastering the Probability & Statistics 1 component of the Cambridge International AS & A Level Mathematics syllabus.
Keywords: Mathematics Education -- AS & A Level Mathematics -- Probability & Statistics